2015
DOI: 10.4136/ambi-agua.1468
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da água superficial por meio de análise do componente principal

Abstract: This study used multivariate techniques for data analysis in order to determine the natural and anthropogenic factors that contribute to the spatial and temporal variations of water quality in urban watersheds of Caxias do Sul, Brazil. Principal Component Analysis (PCA) was used to analyze data collected at 30 points between September 2012 and January 2014. Monitoring was conducted bimonthly in six urban basins, where a total of 21 physical, chemical and biological parameters were analyzed. We found that PCA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
2
4
0
6
Order By: Relevance
“…These results demonstrate that the points with greatest degradation are directly associated with the land use in the urban area of the microbasin and industrial activities. These results are similar to those reported by Finkler et al (2015), who found that the most significant parameters in the water quality variation in watersheds in the municipality of Caxias do Sul were related to anthropic activities and lack of treatment of domestic and industrial effluents, directly causing degradation of the water quality.…”
Section: Relationship Of Water Quality and Land Use And Occupationsupporting
confidence: 91%
“…These results demonstrate that the points with greatest degradation are directly associated with the land use in the urban area of the microbasin and industrial activities. These results are similar to those reported by Finkler et al (2015), who found that the most significant parameters in the water quality variation in watersheds in the municipality of Caxias do Sul were related to anthropic activities and lack of treatment of domestic and industrial effluents, directly causing degradation of the water quality.…”
Section: Relationship Of Water Quality and Land Use And Occupationsupporting
confidence: 91%
“…The multivariate analysis helps in the definition of which variables are more important for water management, assisting in the selection of variables using more objective criteria. This type of statistical analysis is an effective tool in the qualitative evaluation of waters (Vidal and Kiang, 2002;Brito et al, 2006;Cloutier et al, 2008;Palácio, 2009;Fernandes et al, 2010;González et al, 2011;Finkler et al, 2015;Gomes and Cavalcante, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We applied a quantitative approach, through PAST 3 software, to the filtered data using Principal Components Analysis (PCA) (Finkler et al, 2015; Venkata Krishnamoorthy and Reddy, 2019) for the useful images of the Bolonha Lake. In this analysis, we considered the groups of images classified as "lake without cloud cover" and "lake under partial cloud cover" that surpassed the criterion from the cloud interference as useful data; the remaining scenes summed up to not suitable scene data.…”
Section: Conditionmentioning
confidence: 99%